Understanding Teenage Fertility, Cohabitation, and Marriage: The Case of Peru - Favara, M; Lavado, P; Sanchez, A (Institute of Labor Economics, 2016)
In this study, we used data from the Young Lives study, which investigates teenage childbearing, marriage, and cohabitation by tracking a cohort of individuals from the ages of 8 to 19 years. While the present analysis does not intend to establish causality, the longitudinal nature of the data allows us to identify the combination of early circumstances and life changes that induce a higher likelihood of these events. The analysis addresses bias both due to reverse causality and community characteristics that are usually unobserved and fixed over time, a strategy that is quite unique in studies of developing countries. About 1 out of 5 females (and 1 out of 20 males) in our sample had at least one child by the age of 19, and 80 percent of them were married or cohabiting. Early marriage/cohabitation is indeed intrinsically related to early pregnancy and largely predicted by the same factors. For females specifically, girls from poor households with an absent parent for a prolonged period have a higher risk of early childbearing. Similarly, girls whose self-efficacy and educational aspirations decrease over time are more at risk of becoming a mother during adolescence. Conversely, school attendance and better school performance predict a lower risk of early pregnancy; our analysis suggests that this is largely because it postpones the first sexual relationship.